Scientific effects of Triple Helix interactions among research institutes, industries and universities - Zhang, Y; Chen, K; Fu, X (Elsevier, 2019)
The Triple Helix (TH) interactions among innovation organizations have become increasingly important for national science and technology development. Yet, few studies in the extant literature have investigated their effects on the participants' scientific performance. This study fills in this research gap by exploring whether the scientific performance of research institutes is influenced by their TH interactions with industries or/and universities. More specifically, the dynamic patterns of bilateral and trilateral interactions of the Chinese Academy of Sciences (CAS) as a typical example with industries or/and universities, as well as their effects on the CAS's scientific performance are revealed by means of the TH theoretical framework. The research result shows that their bilateral and trilateral interactions not only directly and significantly improved the CAS's scientific performance but also moderately enhanced the effects of research investments on that performance. It is confirmed as expected that the bilateral interactions between research institutes and universities exhibit a more positive and significant effect on scientific performance in both direct and indirect ways compared with the bilateral interactions between research institutes and industries. In summary, this study extends the analytical scope of TH empirical studies by implementing an exploring research on the TH effects from the perspective of academic institutes.